Multiple cases of cutaneous Mycobacterium massiliense infection in a "hot spa" in Japan - Nakanaga, Kazue; Hoshino, Yoshihiko; Era, Yuko; Matsumoto, Kentaro; Kanazawa, Yuji; Tomita, Atsuko; Furuta, Masanari; Washizu, Motohisa; Makino, Masahiko; Ishii, Norihisa (Journal of clinical microbiology, 2011)
Seven body polishers working in the same "hot spa" presented with multiple red nodules and papules on their hands and forearms. A causative agent was successfully isolated from two of the subjects and from a swab sample collected from the underside of a bed cover in the body-polishing facility. The two cutaneous isolates and the environmental isolate were rapidly growing mycobacteria that formed nonphotochromogenic smooth or smooth/rough colonies on Ogawa egg slants. They were identified as Mycobacterium massiliense by multigenotypic analysis using the 16S rRNA, hsp65, and rpoB genes and the 16S-23S rRNA internal transcribed spacer (ITS) region. However, the use of the 16S rRNA gene sequence and/or DNA-DNA hybridization (DDH Mycobacteria Kit) alone would not distinguish M. massiliense from mycobacteria in the M. chelonae-M. abscessus group. The three isolates were significantly more susceptible to clarithromycin, doxycycline, and minocycline than the M. abscessus and M. bolletii reference strains. One cutaneous isolate and the environmental isolate were in a related cluster by randomly amplified polymorphic DNA PCR (RAPD-PCR). Of the several mycobacterial species found in the day spa, only M. massiliense was isolated from biopsy specimens of the skin lesions, suggesting that this bacterium is a human skin pathogen. This is the first known report of cutaneous M. massiliense infections that could not be attributed to a prior invasive procedure. This is also the first report of M. massiliense infection in Japan.